2015
DOI: 10.1007/s10461-015-1206-8
|View full text |Cite
|
Sign up to set email alerts
|

Pain and Mortality Risk in a Cohort of HIV-Infected Persons with Alcohol Use Disorders

Abstract: Pain has been associated with increased risk for mortality in some studies. We analyzed data from a cohort study [HIV-longitudinal interrelationships of viruses and ethanol (HIV-LIVE)] of HIV-infected persons with alcohol use disorders enrolled 2001–2003 to explore whether reporting moderate or greater pain interference was associated with mortality. The main independent variable was pain that at least moderately interfered with work based on a single question from the SF-12. Primary analyses dichotomized at “… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
0
4
0
2
Order By: Relevance
“…Heavy drinking in this population is also associated with engagement in risky health behavior, such as cigarette (18,19) and substance use (20), which can lead to other chronic illnesses. Some studies have found that PLWH who use alcohol have increased chronic comorbidity (5,10,21,22), while other studies have found no such association (3,2325). Others have found a J-curve association between alcohol consumption and risk for chronic illness.…”
Section: Introductionmentioning
confidence: 99%
“…Heavy drinking in this population is also associated with engagement in risky health behavior, such as cigarette (18,19) and substance use (20), which can lead to other chronic illnesses. Some studies have found that PLWH who use alcohol have increased chronic comorbidity (5,10,21,22), while other studies have found no such association (3,2325). Others have found a J-curve association between alcohol consumption and risk for chronic illness.…”
Section: Introductionmentioning
confidence: 99%
“…Faktor klinis berupa jumlah CD4, fase klinis dan pengobatan Anti-Retroviral (ARV) dan infeksi oportunistik merupakan salah satu faktor internal yang dialami seseorang. Dalam tiga penelitian yang dilakukan oleh Azagew, Woreta, Tilahun, dan Anlay (2017); Lawson et al (2015); dan Tsui et al (2016) jumlah CD4 yang lebih rendah tidak memiliki hubungan dengan adanya rasa sakit yang dialami oleh ODHA.…”
Section: Pembahasanunclassified
“…In addition to chronic pain, PLHIV have also reported mental health and harmful substance use issues [ 6 , 8 ]. Generally, PLHIV experiencing mental health problems such as anxiety and depression are also more likely to report increases in pain [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%